Frictional half-plane contacts in partial slip in the steady-state - Andresen, HN (2020)
This thesis aims to understand how a number of real contact problems respond to local contact loads during cyclic loading and which combination of loads will give rise to a state of partial slip. At the core of this thesis lies a family of partial slip solutions for half-plane contact problems subject to different forms of periodic loading. This collection of partial slip solutions allows engineers and researchers alike to assess rapidly the contact behaviour, namely the position and extent of the zones of relative cyclic motion along the interface. While knowing the slip stick pattern, by itself, does not answer the question of whether an assembly is prone to fretting fatigue or not, it enables the user to set up simple laboratory experiments in order to determine the fretting fatigue strength of the design under consideration.